Quarterly National Accounts (Edition 2012/1) (OECD National Accounts Statistics, 2012)
This dataset presents OECD quarterly national accounts (QNA) statistics collected from all the OECD member countries and some major economies. It contains a wide selection of mainly seasonally adjusted quarterly series such as gross domestic product (GDP) expenditure and output approaches, GDP income approach, gross fixed capital formation, disposable income and real disposable income components, saving and net lending, population and employment, employment by industry, compensation of employees, household final consumption expenditure by durability. Data are expressed in millions of national currency, millions of US dollars and other measures and starting from 1946 when available